STUDI PENGARUH EKSTRAK ECENG GONDOK SEBAGAI INHIBITOR KOROSI UNTUK PIPA BAJA SS400 PADA LINGKUNGAN AIR - Indrayani, Novi Laura (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2016)
Corrosion is the main causes of construction failure of a bridge. Isolating the metal from corrosion substances is the most effective way to prevent corrosion in this construction. The usage of natural corrosion inhibitor is an alternative way to achieve that goal. Natural substance is chosen as an alternative because it is safe and widely available, biodegradable, low cost, and environmentally friendly. This work was conducted to study the inhibition behavior of water hyacinth extract. Chemical compounds in water hyacinth are cellulose and lignin. Lignin is an oxidation agent. This work use carbon steel SS400 and the effect of water hyacinth extract to the corrosion was studied. The works were conducted in liquid base and liquid acid with the variable of inhibitor concentration. Analysis was conducted by using weigh loss method and in base liquid the best concentration was 0.20 M as 0.0020 mpy and in acid liquid as 0.0047 mpy.The decrease occur because the extract works by forming thin layer (investigated on SEM analysis) or complex compound, which adsorb on metal surface as protection layer which can prevent the reaction of metal with its environment.